Analisis Peran Jenis Pekerjaan dan Fasilitas IT Pendukung terhadap Produktivitas Kerja Karyawan Work From Anywhere - Nadya Nur Fadhila; Diah Priharsari; Fajar Pradana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
During the global COVID-19 pandemic information systems have overcoming the limitations of interaction when working, which is considered a digital transformation, such as the Work From Home policy, which is currently shifting to the WFA (Work From Home) work system. anywhere). The existence of this new work system certainly has an impact on employee work productivity which is influenced by several factors, especially technology. In this study, the factors that will be examined are the type of work and IT facilities owned by WFA employees through the Exploratory Mix Method. By conducting a Thematic Analysis, the results show that the type of work can be seen from the existence of work flexibility policies and the frequency of interaction needs which can cause overtime on the job, and in IT facilities it is found that the company's role in fulfilling IT facilities can increase productivity. To confirm the qualitative findings, a quantitative study was carried out through a questionnaire with 115 respondents, through the multiple linear regression analysis method, it was found that the final result of this study was on the type of work of employees during WFA who had work time flexibility coupled with a high frequency of interaction between employees who tended to make these employees work overtime and this has a significant effect on work productivity. Then for IT facilities, the company's role in fulfilling IT facilities in order to have standardized devices that have been determined, then these employees must have self-motivation in working to achieve increased work productivity.